Analizing UPNVJ Political Science Students Perception Of "Oke Gas" Political Branding On TikTok In The Context Of Prabowo Subianto's Presidential Campaign - Imperanur, Aura Hallyka; Indrawan, Jerry (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study explores the perceptions of Political Science students at UPNVJ regarding the “Oke Gas” campaign content on TikTok as part of Prabowo Subianto’s political branding strategy during the 2024 presidential election. Employing a descriptive qualitative method, the research investigates how students interpret the use of populist, symbolic, and visual communication in digital political campaigns. Findings indicate that students view the strategy as an adaptive response to the youth-dominated voter demographic, yet remain divided in their assessments some consider it effective, while others perceive it as superficial rebranding that prioritizes personal image over policy substance. The research also highlights students’ concerns about the potential decline in deliberative democratic quality due to emotionally driven content.TikTok’s role as a fast-paced, interactive platform is acknowledged as effective in disseminating political messages, but it also raises critical questions about the balance between virality and substantive political discourse. Political Science students, equipped with analytical frameworks and democratic awareness, are positioned not merely as campaign targets but as active evaluators of political strategy. Their perceptions are shaped by media ecology, youth political orientation, and the tension between electoral marketing and participatory democratic ideals. This study contributes to understanding how political branding in the digital age is received by an increasingly critical and digitally literate electorate.